Upaya Pencegahan Tuberkulosis Anak di Kelurahan Koto Baru Nan XX Lubuk Begalung Kota Padang - Haq, Arinil; Basra, Mega Utami; Khairatih, Maisyatil; Oktafiani, Sinta (Universitas Baiturrahim, 2024)
Tuberculosis (TB) in children (aged 0-14 years) is a disease caused by the bacteria Mycobacterium tuberculosis. WHO estimates that in 2021 as many as 10.6 million people will be infected with TB worldwide. Six million of them are men, 3.4 million women and 1.2 million children. This community service was carried out at the Koto Baru Nan XX Village Head Office with 20 health cadres on duty at the posyandu. Community service activities consist of education about childhood TB. Apart from that, a pre-test and post-test were also carried out to determine the level of knowledge of community service participants before and after the training. The data was then analyzed using the Wilcoxon test. It is known that there is a significant difference between the level of knowledge before and after counseling regarding pediatric TB among health cadres in Koto Baru Nan XX Lubuk Begalung Village, Padang City. It is hoped that with this activity, health cadres can convey this knowledge to the community, including those present at the posyandu which is held once a month.